Personalization Methods for Internet Portals - Barbara Dębska; Agnieszka Kubacka (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
The article presents methods of acquiring and gathering data about users of internet portals, with particular emphasis on educational portals. Definitions, aims and tasks related to the process of personalization of e-learning portals are thoroughly discussed. So are knowledge acquisition techniques applied in personalization, especially artificial intelligence methods.